Perceptions of human papillomavirus vaccination among adolescent boys and their parents in high-income countries: a scoping review protocol - Eunyoung Park; Hyun-Ju Seo; Yumi Choi; Jisu Seo; Hye-Jeong Yang (BMJ Open, 2025)
Background Human papillomavirus (HPV) is the most common cause of cervical cancer in women. However, among adolescent boys, initial exposure to HPV is associated with a higher risk of developing oropharyngeal and oral cancers compared with girls. Notably, the incidence of oropharyngeal cancer has been rising sharply in high-income countries, yet HPV vaccination coverage among adolescent boys remains suboptimal. Therefore, understanding the perceptions of adolescent boys and their parents regarding HPV vaccination in high-income countries is crucial for the development of effective public health strategies.Objectives This scoping review aims to explore the perceptions of adolescent boys and their parents regarding HPV vaccination and investigate the facilitating factors and barriers influencing HPV vaccination.Methods and analysis The method framework of Arksey and O’Malley, the Joanna Briggs Institute, as well as the recommendations of Levac will be used to conduct the scoping review. This scoping review will be reported in accordance with the PRISMA extension for scoping reviews checklist. A systematic literature search will be performed on Ovid-MEDLINE, CINAHL, Cochrane CENTRAL, Ovid-Embase, PsycINFO and Web of Science. Two reviewers will independently perform the study selection and data extraction. Identified studies will be extracted using a customised extraction template on Covidence and analysed descriptively using narrative synthesis. The review commenced in April 2024 and will be completed in July 2025.Ethics and dissemination Formal ethical approval is not required, as primary data will not be collected for this study. The findings will be disseminated through publication in a peer-reviewed journal.Registration This protocol has been registered with the Open Science Framework (https://doi.org/10.17605/OSF.IO/M5NH2).